The contribution of Social Islami Bank Limited on the exports and imports of traditional and non-traditional items of Bangladesh - Ferdous, Rafia (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.